PELATIHAN KEBUGARAN JASMANI SISWA DI KABUPATEN SUMENEP PADA MASA PANDEMI COVID 19 - Abdul Azis; Dian Helaprahara; Andi Fepriyanto; Nugroho Agung Supriyanto (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2021)
Community service activities with the theme of physical fitness training for students in Sumenep during the Covid 19 pandemic season aim to provide understanding and awareness to students of the importance of maintaining physical fitness so that viruses do not easily attack the body. This activity uses a web-based training approach using the zoom application and this activity is carried out for one day with two sessions, namely a theory session and a practical session. The results of this activity can be seen from the large number of participants and the high enthusiasm of the participants with the many questions asked, besides that there is an increase in knowledge and ability to do push ups correctly according to the procedure, Besides that, the enthusiasm of students in participating in this activity is quite high, it’s can be seen from the level of satisfaction of participants in participating this activity reaching 61% of 79 participants.